How Private Higher Education Institutions in Indonesia Changed Their Marketing Mix amidst the COVID-19 Pandemic - Andamar Pradipta (International Journal of Educational Management and Innovation, 2022)
The COVID-19 pandemic has significantly affected industries to amass consumers, with the education industry not being an exception. For-profit higher education institutions (HEIs) in Indonesia were forced to rethink their marketing strategies amidst COVID-19 restrictions and a changing economy. Five private HEIs from four different cities in Indonesia have been the subjects of this study, focusing on how parents' demands and the pandemic drove changes in these HEIs' 7P marketing mix. In-depth interviews were conducted with representatives of these HEIs' marketing teams. It was found that three of the seven Ps in the HEIs, as mentioned above,' marketing mix, were changed (price, promotion, and process). It was concluded that Indonesian HEIs bear a distinct producer-consumer relationship that hinders patrons from making demands as freely as they would with other types of services. Future research should then look into this newly-discovered producer-consumer dynamic in other levels of education.